Intending Scotland : explorations in Scottish culture since the Enlightenment - Craig, Cairns (Edinburgh University Press, 2009)
Intending Scotland reconsiders our understanding of the development of Scottish culture from the Enlightenment to the present day. The book recovers and reconnects Scottish thinkers from Hume and Reid in the eighteenth century, to Andrew Seth, Norman Kemp Smith and John Macmurray in the late nineteenth and twentieth centuries. It contextualises their work in relation to the development of Scottish anthropology and psychology, from which emerged, in the work of Ian Suttie and R. D. Laing, some of the most significant challenges to Freudian psychology. Craig uses this Scottish tradition to challenge theories of the nation over the last thirty years, providing critiques of Bhabha's 'hybridity' and of Anderson's 'imagined community', and of theories of 'the Other' within a postcolonial framework. Ranging over Scotland's intellectual and cultural history across three centuries, taking in gardens and gardeners as well as historians and historiographers, scientists and engineers as well as philosophers and psychologists, Intending Scotland presents a reinterpretation of Scottish cultural life as radical as the developments in the nation's contemporary politics. Key Features. Challenges negative conceptions of the Scottish cultural past and of the failures of Scotland's cultural development Sets Scotland's recent political development in the context of its cultural achievements in the twentieth century Deals with major figures in Scottish culture - Hume, Reid - and shows how our modern understanding of them is dependent on the work of later Scottish thinkers Engages with prominent critics in contemporary theory -- Anderson, Derrida, Bhabha, Kearney -- and develops a critique of them from a Scottish perspective.